Exploring use of the Outcomes Framework for Dance Movement Therapy to establish a group profile and objectives for psychomotor therapy interventions. Issue 4 (1st October 2020) - Lebre, Paula; Dunphy, Kim; Juma, Soraia
ABSTRACT: Fields of psychomotor therapy and dance movement therapy share a common challenge in the under-development of accessible assessment instruments that are easy for practitioners to use and relevant for diverse client groups. This study discusses the application of the Outcomes Framework for Dance Movement Therapy as an assessment tool in a community psychomotor therapy programme for adults with high support needs in Almada, Portugal. The Framework was trialled to create a group profile to support the development of therapeutic objectives for the entire group. 61 participants were observed by four raters across a series of sessions. Group profile results were obtained by averaging scores from sub-domains and 59 individual items for each participant, after an internal consistency test found acceptable to good reliability values. Findings indicate the Framework was suitable for use by psychomotor therapists to develop a group profile and set program objectives.